correct option is b) {y : -5 < x < - 1 }

Step-by-step explanation:

The graph of function y = ∛-x -3 over the domain of {x : -8 < x < 8 } is shown in figure-1

Range is set of Y values for which the function is define.

So, in order to find the range , we need to find the corresponding y values for given domain.

Put x = -8 in y = ∛-x -3 then we get,

y = ∛-x -3

y = ∛-(-8) -3

y = ∛8 -3

y = 2 -3

y = - 1

Put x = 8 in y = ∛-x -3 then we get,

y = ∛-(8) -3

y = ∛-8 -3

y = -2 -3

y = - 5

Hence the range of function y = ∛-x -3 over the domain of {x : -8 < x < 8 } is

{y : -5 < x < - 1 }

correct option is b) {y : -5 < x < - 1 }

correct option is b) {y : -5 < x < - 1 }

Step-by-step explanation:

The graph of function y = ∛-x -3 over the domain of {x : -8 < x < 8 } is shown in figure-1

Range is set of Y values for which the function is define.

So, in order to find the range , we need to find the corresponding y values for given domain.

Put x = -8 in y = ∛-x -3 then we get,

y = ∛-x -3

y = ∛-(-8) -3

y = ∛8 -3

y = 2 -3

y = - 1

Put x = 8 in y = ∛-x -3 then we get,

y = ∛-(8) -3

y = ∛-8 -3

y = -2 -3

y = - 5

Hence the range of function y = ∛-x -3 over the domain of {x : -8 < x < 8 } is

{y : -5 < x < - 1 }

correct option is b) {y : -5 < x < - 1 }

Five-number summary in ascending order: Step-by-step Explanation:The number summary, in ascending order, includes the minimum value, maximum value, median value, upper quartile and...Read More

2 more answers

this linear equation would have just one solution. step-by-step explanation: the reason why this would have one solution is that it is an expression with just one variable. since t...Read More

2 more answers

I dotted number line would represent the solution...Read More

3 more answers

the answer would be 150 books step-by-step explanation: if you divide 300 by 2 you will get 150...Read More

1 more answers

afjnawenkfnjaw; enkanwelwaklalejjaw; fijstep-by-step explanation:...Read More

1 more answers

thus, the first answer choice, y = sec x, is the correct one...Read More

2 more answers

let's solve your equation step-by-step. 24−3x=−27 step 1: simplify both sides of the equation. 24−3x=−27 24+−3x=−27 −3x+24=−27 step 2: subtract 24 from both sides. −3x+24−24=−27−...Read More

2 more answers

b is the answer that makes most sensestep-by-step explanation:...Read More

1 more answers

- Solving systems review sheet...
- PLZ HELP The net of a solid is shown below: Net of a square pyramid sh...
- There is a 50-50 chance that the queen carries the gene for hemophilia...
- A bag has 7 red marbles and 8 yellow marbles. Half of the yellow marbl...
- MARK BRAINLIEST AND LOTS OF POINTS PLZ HELP...
- The starting salaries of individuals with an MBA degree are normally d...
- What is the discriminant of the polynomial below?2x + 47-9...
- The Bradenton Post polled 1,356 adults in the city to determine whethe...
- -3(-4n + 30) = -30 Answer please?...
- Advanced question! I need smart people...